MODERN TEACHING METHODS AND THEIR EFFECT ON STUDENT ACHIEVEMENT - Ko`shkinova Aynash Garifulla Qizi; Khamitov Eldorbek Erkinovich (TADQIQOTLAR, 2026)
ABSTRACT: Modern education is undergoing rapid transformation due to social, technological, and pedagogical changes. Traditional teacher-centered approaches are gradually being replaced by learner-centered and interactive teaching methods designed to enhance student achievement. This article explores modern teaching methods such as problem-based learning, collaborative learning, blended learning, and technology-enhanced instruction, and examines their impact on students’ academic performance, motivation, and critical thinking skills. The study is based on an analytical review of contemporary scholarly literature and provides an original academic discussion of how innovative pedagogy contributes to improved learning outcomes.